1992
DOI: 10.2337/diab.41.12.1562
|View full text |Cite
|
Sign up to set email alerts
|

Insulin Induces the Translocation of GLUT4 From a Unique Intracellular Organelle to Transverse Tubules in Rat Skeletal Muscle

Abstract: Skeletal muscle surface membrane is constituted by the PM domain and its specialized deep invaginations known as TTs. We have shown previously that insulin induces a rapid translocation of GLUT4s from an IM pool to the PM in rat skeletal muscle (6). In this study, we have investigated the possibility that insulin also stimulates the translocation of GLUT4 proteins to TTs, which constitute the largest area of the cell surface envelope. PM, TTs, and IM components of control and insulinized skeletal muscle were i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
105
1
1

Year Published

1995
1995
2016
2016

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 139 publications
(116 citation statements)
references
References 0 publications
9
105
1
1
Order By: Relevance
“…In addition, the PKC isoform z previously shown to be activated by insulin was not changed providing further support for the inhibition of the early steps of insulin signalling cascade [32]. Noteworthy, in contrast to an insulin-dependent GLUT4 translocation [12,13,14], we observed no translocation of GLUT4 to Table 5. Quantification of the effect of glucose infusion on PKC isoforms translocation.…”
Section: Discussionsupporting
confidence: 73%
“…In addition, the PKC isoform z previously shown to be activated by insulin was not changed providing further support for the inhibition of the early steps of insulin signalling cascade [32]. Noteworthy, in contrast to an insulin-dependent GLUT4 translocation [12,13,14], we observed no translocation of GLUT4 to Table 5. Quantification of the effect of glucose infusion on PKC isoforms translocation.…”
Section: Discussionsupporting
confidence: 73%
“…For example, immunoelectron microscopy has demonstrated the predominant localization of GLUT4 protein (∼60%) in tubulo-vesicular elements beneath the plasma membrane with the remaining protein localized to the trans-Golgi network (TGN), clathrin-coated vesicles and to endosome structures. [18][19][20][21]. The content of GLUT4 in all these compartments was found to decrease in response to insulin concomitant with an increased distribution to the plasma membrane.…”
Section: Glut4 Intracellular Retention and Exocytosismentioning
confidence: 88%
“…In part this is because at steady-state GLUT4 is distributed at varying levels throughout most of the endomembrane system [17][18][19][20][21]. Indeed, following insulin-stimulated translocation, GLUT4 is retrieved from the plasma membrane by endocytosis and routed through a complex trafficking itinerary that appears to include endosome compartments and perhaps the trans-Golgi network, before returning to the IRC.…”
Section: Glut4 Intracellular Retention and Exocytosismentioning
confidence: 99%
“…Skeletal muscle expresses both the GLUT1 and GLUT4 glucose transporters but it is the mobilization of GLUT4, from an intracellular store to the plasma membrane (PM), that explains the observed increase in glucose transport in response to insulin binding [5][6][7][8]. In contrast, GLUT1 expression is largely restricted to the PM where, under normal *Corresponding author.…”
Section: Introduction 2 Materials and Methodsmentioning
confidence: 99%
“…Little is known regarding the nature and identity of the intracellular compartments containing the GLUT4 transporter and the subunits of the Na,K-ATPase. However, subcellular fractionation studies have revealed that the insulin-induced loss of both GLUT4 and the ~2-Na,K-ATPase subunit occurs from intracellular membranes (IM) of the same buoyant density [7,12]. This observation may signify that these proteins are colocalized in a single intracellular pool enabling them to be recruited to the PM simultaneously upon insulin stimulation.…”
mentioning
confidence: 99%